2015
DOI: 10.3390/v7122932
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete LPS Core-Specific Felix01-Like Virus vB_EcoM_VpaE1

Abstract: Bacteriophages represent a valuable source for studying the mechanisms underlying virus-host interactions. A better understanding of the host-specificity of viruses at the molecular level can promote various phage applications, including bacterial diagnostics, antimicrobial therapeutics, and improve methods in molecular biology. In this study, we describe the isolation and characterization of a novel coliphage, vB_EcoM_VpaE1, which has different host specificity than its relatives. Morphology studies, coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…A set of three myophages were homologous to VpaE1 (88,403 bp), a member of the FelixO1virus genus, which can replicate over a wide range of temperatures (from 9 to 45°C), and has 55 tem perate phages (17 sequenced) ev298 ev159 ev291 ev279 ev302 ev269 ev148 ev167 ev227 ev247 ev236 ev128 ev002 ev034 ev120 Lambda_ev203 ESSI2_ev040 ev130 ev193 ev153 ev201 ev210 Lambda_ev245 ESSI2_ev129 Lambda_ev058 Lambda_ev017 ev027 Lambda_ev207 mEp460_ev081 Evi ev086 ev143a ev179 ev169 ev310 ev173 ev241 ev214 Lambda_ev099 ev251 ESSI2_ev015 ev192 ev141 ev171 Fraca Lambda_ev243 Lambda_ev110 Lambda_ev087 ev314 ESSI2_ev239 ev143b Lambda_ev066 VpaE1_ev035 Gluttony_ev152 Stevie_ev116 T4_ev240 ev183 VpaE1_ev078 ev169 ev177 rv5_ev168 T5_ev219 VpaE1_ev108 ev220 T5_ev212 ev232 T4_ev151 rv5_ev146 rv5_ev158 phAPEC8_ev052 rv5_ev147 rv5_ev156 Lambda vir Ω8 MS2 121Q I2-2 phiX174 PR772 T1 T3 T4 T5 T7 1 0 0 1 1 1 1 1 1 1 1 1 1 1 1 1 2 2 2 2 2 2 2 2 2 2 4 4 4 4 4 4 4 5 5 6 9 11 12 12 13 15 15 16 18 24 27 29 38 40 40 42 42 60 62 66 68 0 0 0 1 1 2 2 7 8 8 8 8 17 30 37 . For example, its receptor is composed of a truncated core LPS.…”
Section: Resultsmentioning
confidence: 99%
“…A set of three myophages were homologous to VpaE1 (88,403 bp), a member of the FelixO1virus genus, which can replicate over a wide range of temperatures (from 9 to 45°C), and has 55 tem perate phages (17 sequenced) ev298 ev159 ev291 ev279 ev302 ev269 ev148 ev167 ev227 ev247 ev236 ev128 ev002 ev034 ev120 Lambda_ev203 ESSI2_ev040 ev130 ev193 ev153 ev201 ev210 Lambda_ev245 ESSI2_ev129 Lambda_ev058 Lambda_ev017 ev027 Lambda_ev207 mEp460_ev081 Evi ev086 ev143a ev179 ev169 ev310 ev173 ev241 ev214 Lambda_ev099 ev251 ESSI2_ev015 ev192 ev141 ev171 Fraca Lambda_ev243 Lambda_ev110 Lambda_ev087 ev314 ESSI2_ev239 ev143b Lambda_ev066 VpaE1_ev035 Gluttony_ev152 Stevie_ev116 T4_ev240 ev183 VpaE1_ev078 ev169 ev177 rv5_ev168 T5_ev219 VpaE1_ev108 ev220 T5_ev212 ev232 T4_ev151 rv5_ev146 rv5_ev158 phAPEC8_ev052 rv5_ev147 rv5_ev156 Lambda vir Ω8 MS2 121Q I2-2 phiX174 PR772 T1 T3 T4 T5 T7 1 0 0 1 1 1 1 1 1 1 1 1 1 1 1 1 2 2 2 2 2 2 2 2 2 2 4 4 4 4 4 4 4 5 5 6 9 11 12 12 13 15 15 16 18 24 27 29 38 40 40 42 42 60 62 66 68 0 0 0 1 1 2 2 7 8 8 8 8 17 30 37 . For example, its receptor is composed of a truncated core LPS.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, DNA fragment containing BREX genes was amplified from E. coli HS genome (positions 340 696–354 491, NC_009800.1) using TS551/TS552 primers. This pBREXAL plasmid was used in plaque assays using phages T4, T4147 (unglycosylated 5-hmC-containing T4 mutant was kindly provided by Dr Lindsay W. Black (23)), vB_EcoM_VR5 (VR5), vB_EcoM_VR7 (VR7) (24) and vB_EcoM_VpaE1 (VpaE1) (25) phages.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that high phage concentrations could induce pro-inflammatory responses, while long-term exposure to phages induced an antibody response in the spleen (Hodyra-Stefaniak et al 2015;Majewska et al 2015). Therefore, an appropriate purification protocol is mandatory to reduce endotoxin levels to satisfy the requirements for phage clinical application (Simoliunas et al 2015). This study analyzed the abundance and distribution of orally administrated phages in the gastrointestinal tract when mice were exposed to a lytic and a lysogenic phage Fig.…”
Section: Discussionmentioning
confidence: 99%